2021
DOI: 10.1016/j.bbih.2021.100201
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of tryptophan metabolism in MS beyond neuroinflammation and neurodegeneration: A paradigm shift to neuropsychiatric symptoms

Abstract: The metabolism of tryptophan through the kynurenine pathway (KP) has been increasingly recognised in contributing to disease progression in the autoimmune and inflammatory disease multiple sclerosis (MS). In this review, the roles of inflammation and the KP are recontextualised to better understand the aetiology of the neuropsychiatric symptoms (depression, postpartum depression, suicidality, fatigue and cognitive dysfunction) in MS. These symptoms will be discussed in the context of cytokine-induced sickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…In line with our findings, decreased TRP levels in plasma obtained from pwMS have been previously reported [31,32]. Recent studies have shown that activation of the kynurenine pathway (KP), responsible for more than 95% of TRP degradation, plays a key role in MS pathogenesis by modulating cell-mediated immune responses and may be associated with disease progression [33,34]. Lim et al found decreased serum TRP concentrations and a significantly higher kynurenine/tryptophan ratio in pwMS compared to HCs, and this was more pronounced in those with progressive disease types, suggesting that abnormalities in the KP may be associated with the conversion from early-mild stage to progressive MS forms, which is consistent with our findings [35].…”
Section: Discussionsupporting
confidence: 90%
“…In line with our findings, decreased TRP levels in plasma obtained from pwMS have been previously reported [31,32]. Recent studies have shown that activation of the kynurenine pathway (KP), responsible for more than 95% of TRP degradation, plays a key role in MS pathogenesis by modulating cell-mediated immune responses and may be associated with disease progression [33,34]. Lim et al found decreased serum TRP concentrations and a significantly higher kynurenine/tryptophan ratio in pwMS compared to HCs, and this was more pronounced in those with progressive disease types, suggesting that abnormalities in the KP may be associated with the conversion from early-mild stage to progressive MS forms, which is consistent with our findings [35].…”
Section: Discussionsupporting
confidence: 90%
“…Our result reflects a broader implication and link with immune regulators such as the aryl hydrocarbon receptor and interactions with the kynurenine pathway in modulating MS progression, relevant to our MS cohort ( Bessede et al., 2014 ; Yan et al., 2010 ). It would be of interest to examine how the kynurenine pathway fits into our current hypothesis considering its role in both mood and immune regulation in MS ( Tan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%